A zeptospace odyssey : a journey into the physics of the LHC - Giudice, Gian Francesco (Oxford : Oxford University Press, 2010)
This book provides an everyman's guide for understanding and following the discoveries that will soon take place at the famous Large Hadron Collider experiments at CERN. The material is presented accurately yet accessibly, and the book is infectious in its enthusiasm for the project.
Includes index.
Description based on print version record.
Keywords: Large Hadron Collider (France and Switzerland) -- Popular works